Hypervirulent Klebsiella pneumoniae Infections in Pediatric Populations in Beijing (2017–2019): Clinical Characteristics, Molecular Epidemiology and Antimicrobial Susceptibility. Issue 12 (15th July 2021) - Li, Yue; Dong, Limin; Gao, Wei; Zhen, Jinghui; Dong, Fang; Yao, Kaihu
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Hypervirulent variants of Klebsiella pnuemoniae (hvKp) are emerging globally causing life-threatening infectious diseases; however, comprehensive studies on pediatric hvKp strains and related infections are still lacking. Methods: Clinical data were collected from medical records. Genotype (multilocus sequence typing), capsular serotype, virulence gene profile and carbapenemase of the isolates were determined by PCR and DNA sequencing. Broth microdilution method was adopted to test the antimicrobial susceptibility. Hypermucoviscosity phenotype and the virulence of the strains were evaluated by string test and Galleria mellonella larvae killing assay. Results: Among 319 K. pneumoniae strains, 26 (8.2%) hvKp were identified, the detection rates in 2017, 2018 and 2019 were 1.8%, 5.2% and 11.3%. The majority of hvKp infections were found in school-age children and adolescents (57.7%). Pneumonia was the most common diagnosis (38.5%). Single fatal case was hvKp caused liver abscess complicated with bacteremia. hvKp were dominated by ST23 (30.8%) and ST11 (30.8%). Eight carbapenem-resistant hvKp (CR-hvKp) were found, which all belonged to ST11. Virulence gene profile revealed that ST11 hvKp might carry incomplete pLVPK-like plasmids, but they exhibited comparable in vivo virulence to the other hvKp. Conclusions: The infections caused by hvKp are not frequent among pediatric populations, but the detection rate of hvKp in pediatric populations is increasing rapidly in recent years. The emerging and dissemination of ST11 CR-hvKp should be monitored continuously.